Multiple Attribute Authorities for Public Cloud Storge using a Robust Auditable Access Control (International Journal of Engineering and Computer Science, 2018)
Data access control is a challenging issue in public cloud storage systems. Ciphertext-Policy Attribute-Based Encryption (CP-ABE) has been adopted as a promising technique to provide ﬂexible, ﬁne-grained and secure data access control for cloud storage with honest-but-curious cloud servers. However, in the existing CP-ABE schemes, the single attribute authority must execute the time-consuming user legitimacy veriﬁcation and secret key distribution, and hence it results in a single-point performance bottleneck when a CP-ABE scheme is adopted in a large-scale cloud storage system. Users may be stuck in the waiting queue for a long period to obtain their secret keys, thereby resulting in low-efﬁciency of the system. Although multiauthority access control schemes have been proposed, these schemes still cannot overcome the drawbacks of single-point bottleneck and low efﬁciency, due to the fact that each of the authorities still independently manages a disjoint attribute set